2013
DOI: 10.1038/ncomms2627
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelic expression of TMPRSS2/ERG in prostate cancer stem cells

Abstract: While chromosomal translocations have a fundamental role in the development of several human leukaemias, their role in solid tumour development has been somewhat more controversial. Recently, it was shown that up to 80% of prostate tumours harbour at least one such gene fusion, and that the most common fusion event, between the prostate-specific TMPRSS2 gene and the ERG oncogene, is a critical, and probably early factor in prostate cancer development. Here we demonstrate the presence and expression of this sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…The 'G' allele, however, is rarely used by the host machinery for transcription. Similar cases have been reported in the TMPRSS2 gene in prostate cancer stem cells [42]. In addition, stochastic monoallelic expression is also widespread in mammalian genomes, including olfactory receptor, V1rb2 receptor, T-cell receptor and immunoglobulin genes, pheromone receptors, p120 catenin, odorant receptors, and protocadherins [43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 74%
“…The 'G' allele, however, is rarely used by the host machinery for transcription. Similar cases have been reported in the TMPRSS2 gene in prostate cancer stem cells [42]. In addition, stochastic monoallelic expression is also widespread in mammalian genomes, including olfactory receptor, V1rb2 receptor, T-cell receptor and immunoglobulin genes, pheromone receptors, p120 catenin, odorant receptors, and protocadherins [43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 74%
“…The cellular composition and proportion of a2b1 hi /CD133 þ , a2b1 hi /CD133 À and a2b1 low , also referred to as stem-like cells, TA cells, and CB cells (12) in the normal prostate epithelium versus prostate cancer epithelium is indeed generally very different (5). For instance, the "driver" stem/ progenitor subpopulation in the human prostate often represents only 0.02% of all prostate epithelial cells (5,41). The increase in absolute expression levels of miR-25 in bulk tissues during prostate cancer progression may, therefore, be indicative of an increase in the proportion of more differentiated, less invasive, miR-25 high luminal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Polson et al [49] demonstrated the presence and expression of TMPRSS2:ERG in PCSCs, which would provide ERG-driven survival advantages. Moreover, ALDH + PCa cells have been shown to exhibit several CSC characteristics such as clonogenicity, migration, tumorigenicity, and propensity to form metastases in vivo [3,10] .…”
Section: Pca Stem Cellsmentioning
confidence: 99%